Surgical, Orthodontic and Prosthodontic Rehabilitation of a Patient with Follicular Ameloblastoma: A Case Report - Sailer, Herman F.; Tarawneh, Fadi; Fourkas, Panagiotis; Antoniades, Dimitrios Z.; Athanasiou, Athanasios E. (European Journal of Dentistry, 2010)
This case report describes the combined surgical, orthodontic and prosthodontic rehabilitation of an adult female patient with a previous history of follicular ameloblastoma, which was treated through partial mandibulectomy and an immediate replacement of missing bone with an autologous calvarial bone graft. Orthodontic treatment was undertaken in order to restore occlusal disturbances and obtain sufficient space for two dental implants and an optimum prosthodontic rehabilitation. (Eur J Dent 2010;4:192-196)
Keywords: Follicular ameloblastoma; Bone graft; Mandibulectomy; Orthodontic treatment